2015
DOI: 10.1370/afm.1798
|View full text |Cite
|
Sign up to set email alerts
|

Peer Coaches to Improve Diabetes Outcomes in Rural Alabama: A Cluster Randomized Trial

Abstract: PURPOSE It is unclear whether peer coaching is effective in minority populations living with diabetes in hard-to-reach, under-resourced areas such as the rural South. We examined the effect of an innovative peer-coaching intervention plus brief education vs brief education alone on diabetes outcomes. METHODSThis was a community-engaged, cluster-randomized, controlled trial with primary care practices and their surrounding communities serving as clusters. The trial enrolled 424 participants, with 360 completing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(126 citation statements)
references
References 21 publications
2
119
1
1
Order By: Relevance
“…The paper by Safford and colleagues shows significant stabilization of cardiovascular risk factors over time for participants receiving peer support compared to controls among African American residents of rural Alabama, an area of great poverty and poorly organized clinical care. 33 Tang and her colleagues have focused on peer support as a way of helping to sustain gains from diabetes self-management education. In an earlier paper concerning peer support for Latinos with diabetes, they showed that both staff community health workers and trained volunteer peer supporters were successful in this.…”
Section: Efficacy and Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Safford and colleagues shows significant stabilization of cardiovascular risk factors over time for participants receiving peer support compared to controls among African American residents of rural Alabama, an area of great poverty and poorly organized clinical care. 33 Tang and her colleagues have focused on peer support as a way of helping to sustain gains from diabetes self-management education. In an earlier paper concerning peer support for Latinos with diabetes, they showed that both staff community health workers and trained volunteer peer supporters were successful in this.…”
Section: Efficacy and Effectivenessmentioning
confidence: 99%
“…Safford and Richman and their colleagues in Alabama have explored the importance of seasonality and changes over time. In addition to applying these perspectives in analyzing their intervention, noted above, 33 Richman has led additional work to outline analytic approaches that accommodate the seasonal and nonlinear, dynamic characteristics of diabetes as well as research challenges common in real world settings such as variability of time between baseline and follow-up measures and secular trends. 40 Peer support and other community-focused interventions, especially those intending to reach populations that more conventional approaches fail to engage, raise a number of ethical issues, including confidentiality and informed consent.…”
Section: Research Challengesmentioning
confidence: 99%
“…22,25,29,[31][32][33][34] The pooled effect in the subgroup of 3 studies with predominantly African American participants showed a similar effect size to that seen in the Hispanic subgroup but was not statistically significant, with an SMD of 0.25 (95% CI, -0.064 to 0.571; P = .11; I 2 = 58.60%). 23,24,28 The differences in effect sizes between ethnicity subgroups were statistically significant, with a between-group P value of .03. Considering together the 7 studies with predominantly minority participants (belonging to minority culture in the country of residence), the pooled effect showed a clinically relevant improvement in HbA 1c level with peer support interventions, with an SMD of 0.266 (95% CI, 0.163-0.369; P <.001; I 2 = 9.24%), which translates to improvement in HbA 1c level of 0.53% (95% CI, 0.32%-0.73%) (Figure 4).…”
Section: Subgroup Analyses Studies With Ethnic or Racial Predominancementioning
confidence: 89%
“…20 Ultimately, 14 articles with RCT designs and 3 cluster RCTs were eligible for inclusion in the meta-analysis, for a total of 4,715 participants. Of the 17 trials, 10 were done in the United States, [21][22][23][24][25][26][27][28][29][30] …”
Section: Study Selectionmentioning
confidence: 99%
“…The design of the study has been described in detail elsewhere. 1 Main study outcomes were changes in glycated hemoglobin (HbA 1c ), body mass index (BMI), cholesterol, blood pressure, diabetes distress, quality of life, and patient activation.…”
Section: Methodsmentioning
confidence: 99%